Development of instrumentation for neuronavigation and transcranial magnetic stimulation - Souza, Victor Hugo de Oliveira e (2018)
Neuronavigation and transcranial magnetic stimulation (TMS) are valuable tools in clinical and research environment. Neuronavigation provides visual guidance of a given instrument during procedures of neurological interventions, relative to anatomic images. In turn, TMS allows the non-invasive study of cortical brain function and to treat several neurological disorders. Despite the well-accepted importance of both techniques, high-cost of neuronavigation systems and limited spatial accuracy of TMS in targeting brain structures, limit their applications. Therefore, the aim of this thesis was to i) develop an open-source, free neuronavigation software, ii) study a possible combination of neuronavigation and 3D printing for surgical planning, and iii) construct a multi-channel TMS coil with electronic control of electric field (E-field) orientation. In the first part, we developed and characterized a neuronavigation software compatible with multiple spatial tracking devices, the InVesalius Navigator. The created co-registration algorithm enabled tracking position and orientation of instruments with an intuitive graphical interface. Measured accuracy was similar to that of commercial systems. In the second part, we created 3D printed models from patients with neurological disorders and assessed the errors of localizing anatomical landmarks during neuronavigation. Localization errors were below 3 mm, considered acceptable for clinical applications. Finally, in the last part, we combined a set of two thin, overlapping coils to allow electronic control of the E-field orientation and investigated how the motor evoked responses depend on the stimulus orientation. The developed coil enabled the stimulation of the motor cortex with high angular resolution. Motor responses showed the highest amplitude and lowest latency with E-field approximately perpendicular to the central sulcus. In summary, this thesis provides new methods to improve spatial accuracy of techniques to brain interventions.